2008
DOI: 10.21000/jasmr08010028
|View full text |Cite
|
Sign up to set email alerts
|

Forest Establishment and Water Quality Characteristics as Influenced by Spoil Type on a Loose-Graded Surface Mine in Eastern Kentucky

Abstract: Six research plots were established on a surface mine for the purpose of evaluating the forest productivity potential and hydrological and water quality characteristics of three different loose-graded spoil types. The three spoil types were: (1) predominately brown, weathered sandstone (BROWN); (2) predominately gray, un-weathered sandstone (GRAY); and (3) mixed weathered and un-weathered sandstones and shale material (MIXED). The average area of the six plots was approximately 3,658 m 2 . The physical and che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 10 publications
(9 reference statements)
4
43
1
Order By: Relevance
“…Previous studies have shown that average tree height and volume were greater on weathered brown sandstone than unweathered gray sandstone (Showalter et al, 2010;Angel et al, 2008;Emerson et al, 2009). Angel et al (2008) reported that average tree height on brown sandstone (66 cm) was significantly greater than average tree height on gray sandstone (35 cm) after 3 years.…”
Section: Treesmentioning
confidence: 92%
See 2 more Smart Citations
“…Previous studies have shown that average tree height and volume were greater on weathered brown sandstone than unweathered gray sandstone (Showalter et al, 2010;Angel et al, 2008;Emerson et al, 2009). Angel et al (2008) reported that average tree height on brown sandstone (66 cm) was significantly greater than average tree height on gray sandstone (35 cm) after 3 years.…”
Section: Treesmentioning
confidence: 92%
“…Angel et al (2008) reported that average tree height on brown sandstone (66 cm) was significantly greater than average tree height on gray sandstone (35 cm) after 3 years. Showalter et al (2010) attributed better tree performance on brown sandstone to lower pH and higher percentage of fines.…”
Section: Treesmentioning
confidence: 97%
See 1 more Smart Citation
“…Amine soil material is a structureless agglomeration of fragmented rock, subsoil, and soil that is often less weathered than the original soil profiles that it has replaced (Angel et al, 2008). Minesoils are formed on landscapes altered by mining processes, particularly by the surface mining operations: The original soil profiles have been disrupted to a depth of at least 1 m, and sometimes partially or completely replaced by earth materials from depths below 1 m (Sencindiver & Ammons, 2000).…”
Section: Mine Soilmentioning
confidence: 99%
“…The type of parent material and rate of weathering are very important in the development and differentiation of soil properties. Mine soils are classified as either Entiols or Inceptisols (Angel et al, 2008;Sencindiver & Ammons, 2000), and are either without natural genetic horizons or with only weak or moderate development (Soil Survey Staff, 1999). After passage of the Surface Mining Control and Reclamation Act (SMCRA) of 1977, mining companies are required to store the original topsoil during the coal mining phase and then return the original topsoil back to the site after the mining is completed.…”
Section: Mine Soilmentioning
confidence: 99%